Tax Planning Value Added Tax (Vat) and Article 4 (2) Tax on Income In Indonesia - Sonbay, Ermida Fermiana; Djamhuri, Ali; Baridwan, Zaki (International Research Journal of Business Studies, 2022)
As the largest source of state budget revenue, the government continually increases tax revenues, one of which is by providing comprehensive tax reforms to the public. The government's goal to maximize revenue in the taxation sector is contrary to the company's goal as a taxpayer, namely, trying to reduce the tax burden to obtain greater profits while still complying with government tax regulations. Hence, companies need to prepare a tax plan. This study aimed to identify the application of tax planning to minimize the payment of Value Added Tax (VAT) and PPh Article 4 Paragraph (2) at PT. BAP in 2013–2017 using qualitative research methods with a case study approach. This study uses a positive qualitative paradigm as a science-based on strict procedures and rules, deductive, nomothetic, relying on sense capture, and value-free. The results of the study showed the application of VAT and Income Tax Planning tax article 4 (2) transfer of land, buildings, and land and buildings in PT. BAP is tax planning by avoiding tax violations, tax planing with delays in crediting input taxes and tax planning through the purchase of bkp with VAT, but the implementation of this tax planning is unsuccessful and inefficient due to lack of knowledge and awareness of paying taxes so as to cause losses to PT. BAP Amounting to IDR 3,340,314,823. Therefore, taxpayers need to have the knowledge and awareness to fulfill their tax obligations in order to carry out tax planning properly.